2004
DOI: 10.1103/physrevlett.92.105504
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Single Vacancy in Achiral Carbon Nanotubes

Abstract: We have performed systematic calculations for single vacancies and their related point defects in achiral carbon nanotubes using a tight-binding model. Our calculations clarify that the local structures around single vacancies in such tubes do reconstruct with no constraint. We find that the structural configuration and formation energy of the resulting point defect are dependent on the radius and chirality, as well as the electric properties of a tube. The electronic structures of the single vacancies also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(148 citation statements)
references
References 25 publications
15
133
0
Order By: Relevance
“…Fig. 1c) shows accordingly that the formation energy of SW-defects and single (V1) and double (V2) vacancies generally decreases as function of curvature in agreement with previous tight-binding [9,10] and DFT calculations [12]. This is particularly evident for the armchair SWCNT, where the formation energy is inversely proportional to the diameter as shown in Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Fig. 1c) shows accordingly that the formation energy of SW-defects and single (V1) and double (V2) vacancies generally decreases as function of curvature in agreement with previous tight-binding [9,10] and DFT calculations [12]. This is particularly evident for the armchair SWCNT, where the formation energy is inversely proportional to the diameter as shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…Fig. 1c) furthermore shows that the formation energy for defects in zigzag nanotubes has a periodic behavior, since the metallic zigzag-tubes have lower formation energy than the semiconducting zigzagtubes, as has been pointed out for V1 and V2 vacancies previously [10,12]. However, Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…1͑b͒-1͑d͒ are formed by removing one-and two-bonded carbon atoms from the pristine SWCNTs, respectively. Consequently, the atoms around the vacancies become undercoordinated, leaving an unsaturated bond termed as dangling bond ͑DB͒, 36 as demonstrated in Fig. 1.…”
Section: Computational Modelmentioning
confidence: 99%
“…It was found that the resistance of CNTs to axial tension deteriorated significantly in the presence of monovacancy and bivacancies. [9][10][11] Tightbinding calculations 36,41 and MD simulations 31 have revealed that the vacancies in the CNTs can undergo bond reconstruction to arrive at a relatively more stable state under elevated thermal environments. By using ab initio calculations, Amorim et al 42 found that the bivacancies are able to alter the charge transport properties of SWCNTs and graphene.…”
Section: Monovacancy and Bivacanciesmentioning
confidence: 99%